Carbon Storage and Sequestration of Urban Street Trees in Beijing, China - Tang, Yujia; Chen, Anping; Zhao, Shuqing (Frontiers in Ecology and Evolution, 2016)
Anthropogenic carbon dioxide (CO2) emissions from cities have significantly increased over the past several decades along with rapid urbanization. To what extent anthropogenic CO2 emissions generated from cities can be offset through conserving or increasing carbon (C) stored within urban areas themselves is a significant scientific question. The role of urban street trees in offsetting anthropogenic CO2 emissions still remains uncertain. Here, using data from field surveys, tree growth measurements and governmental statistical yearbooks, we estimated the C storage and C sequestration capacity of street trees in Beijing. Results showed that the C density and C sequestration rate in Beijing’s urban street trees were about 1/3 ~1/2 of the corresponding magnitudes of non-urban forests in China. However, the total C sequestration of street trees in Beijing’s urban districts was 3.1±1.8 Gg C yr-1 (1 Gg = 109 g) in 2014, equivalent to only about 0.2% of its annual CO2-equivalent emissions from total energy consumption, indicating a rather limited role in offsetting overall anthropogenic CO2 emissions.